DIVERSITY OF SOIL MACRO FAUNA AND ITS ROLE ON SOIL FERTILITY IN MANGLID AGROFORESTRY - Hani, Aditya; Suhaendah, Endah (Indonesian Journal of Forestry Research, 2019)
Soil macro fauna is one of the bio indicators in determining the quality of the land. The total soil macro fauna is influenced by the climatice condition and land utilization pattern. Agroforestry is one of type land utilization that is expected to improve the soil fertility. Land utilization changing from monoculture into agroforestry is predicted to influence the soils macro fauna. This study is aims to find out the population of soil macro fauna before and after applying manglid agroforestry. The research was conducted in Cukangkawung, Tasikmalaya District, West Java Province. Sample of macro fauna was taken from non-productive land of tea plantations and one year after the land was planted by manglid + corn + peanut by using agroforestry. Samples were taken in Feb-March 2015 and once more in Feb-March 2016. The observation land area is 1 hectare that is divided into 1 m x 1 m - 16 observation plots that was placed randomly. In each plot, a hole of 30 cm in depth was made and the dug out soil was placed on the plastic container. The collected macro fauna was counted and placed into a bottle that was filled with 70% alcohol. The macro fauna identification was conducted in LIPI zoology laboratory. The research shows that the diversity indexes for Shanon and Margalef on manglid agroforestry are higher than on the ex tea land.